1998
DOI: 10.1002/(sici)1097-4644(19981201)71:3<313::aid-jcb1>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Collagen in tissue-engineered cartilage: Types, structure, and crosslinks

Abstract: The function of articular cartilage as a weight-bearing tissue depends on the specific arrangement of collagen types II and IX into a three-dimensional organized collagen network that can balance the swelling pressure of the proteoglycan/water gel. To determine whether cartilage engineered in vitro contains a functional collagen network, chondrocyte-polymer constructs were cultured for up to 6 weeks and analyzed with respect to the composition and ultrastructure of collagen by using biochemical and immunochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(136 citation statements)
references
References 50 publications
5
129
0
Order By: Relevance
“…In all of the chondrocyte cultures, pyridinoline cross-link density was lower than that of native articular cartilage [4,16] but did, however, appear to be correlated with the collagen content of the in vitro-formed tissue. This could explain why previous studies have also observed a reduced collagen content as well as lower collagen cross-link density in tissue-engineered cartilage relative to native cartilage [40,42].…”
Section: Discussionmentioning
confidence: 87%
“…In all of the chondrocyte cultures, pyridinoline cross-link density was lower than that of native articular cartilage [4,16] but did, however, appear to be correlated with the collagen content of the in vitro-formed tissue. This could explain why previous studies have also observed a reduced collagen content as well as lower collagen cross-link density in tissue-engineered cartilage relative to native cartilage [40,42].…”
Section: Discussionmentioning
confidence: 87%
“…Nanofibers can be tuned to range from as small as 50 nm up to several microns in diameter, and as such are many times smaller than most mammalian cells; in fact, they are similar in scale to collagen fibers normally present in the ECM. 38 This nano-and micronscale topography has been shown to modulate cell signaling pathways 39 and to elicit superior metabolic and matrix forming activities by seeded cells. 40 Nanofibrous meshes are porous structures with a continuous distribution of pore sizes in the range of 2-465 mm and void volumes of 80-90%.…”
Section: Figmentioning
confidence: 99%
“…There is a substantial medical need for tissues such as skin, cartilage, and bone due to the increasingly aging population and the resulting wear of body parts (6,21,22,25,27,31). For bone replacement surgery, such as revision hip arthroplasty, spine fusions, and jaw augmentation, the currently used bone grafts are mainly from allogeneic or autologous origin.…”
Section: Vol 76 2002 Exploiting Natural Diversity In Adenovirus Tromentioning
confidence: 99%